Gallipoli (Hollywood, Calif. Paramount, 1981)
Two young men in the Australia army in 1915 become part of the legendary World War I confrontation between the German allied Turks and Australia
Mel Gibson, Mark Lee, Bill Kerr, Harold Hopkins, Bill Hunter, Robert Grubb, John Morris, Tim McKenzie, David Argue.
Englisgh subtitles, Spanish Subtitles.
Keywords: World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula